POWER RELATIONS AND THERAPEUTIC CARE - Maria Ribeiro Lacerda (Universidade Federal do Paraná, 1999)
This is a thougth-provoking essay about the power relations which are developed and take place between nurse and his/her clients - the therapeutic care. It aims to contribute to the understanding of the forces which may hinder at the moment of our major professional role performance - the nursing care. The nursing professional develops a relationship whenever he or she delivers care to and along with the client and his/her significant beings, once there is an attitude exchange such as the allowance and the consent to render caring actions which bring about comfort, recovery and rehabilitation. When nurse and client meet, a power relation is established: not only the power granted him/her but also the power the nurse shares or expands. Thus, there is an exchange of experienced knowing between them.